Public Work - an International Outlook - Cseh-Papp, Imola; Wiwczaroski, Troy B.; Csapóné Riskó, Tünde (Applied Studies in Agribusiness and Commerce, 2018)
Labour market policy includes active and passive labour market programmes, aiming to solve different problems. Active labour market programmes assist the unemployed to find jobs and thus return to the labour market. Passive labour market programmes assist the unemployed by providing various kinds of aid, easing social tensions. Public work can be considered to be an active labour market programme, assisting people who receive social care with income based on public beneficial work. Consequently, public work is justified by some on the basis that it is purported to have some kind of moral foundation, as well as because it supposedly shows results within a short time. Yet, the rationale behind using public work programmes to fight unemployment is contested. Detractors see them as being rather costly, questioning their success and arguing that their overall results are uncertain, especially in the long run. In short, there are in fact pros and cons to using public work, with opinions being rather divisive. This study summarises these pros and cons, analysing the relevant international and Hungarian literatures in the context of active labour market programmes. JEL Classification: I38